PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT TERHADAP KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN PKN DI KELAS IV SD IT RAHMAT MARINDAL - Agustin, Bella; Muhammad Faisal Husna; Rita Destini; Nila Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the effect of the TGT model on student learning activity in civics learning in grade IV of SD IT RAHMAT Marindal. This study uses a quantitative approach. The research design used is One Group Pretest-Postest. The subjects in this study were material experts, namely lecturers, grade IV teachers at SD IT RAHMAT Marindal To determine the response to the feasibility of the Teams Games Tournament learning model on student activity in civics subjects. The object of this study is the Teams Games Tournament Learning Model on the material of my country Indonesia. This learning model is designed to help students understand the learning material. The results of this study are based on the average student learning scores, it was obtained that student learning activity in civics subjects increased using the Teams Games Tournament learning model on the material of my country Indonesia in grade IV of SDIT RAHMAT Marindal in the 2024/2025 academic year. From the results of the study, it was obtained that student learning activity in civics subjects increased using the Teams Games Tournament learning model on the material of my country Indonesia in grade IV of SD IT RAHMAT Marindal. This can be seen from the increase in the average number of students who completed meeting 1 and meeting II, namely from 1 (4.76%) students who completed meeting 1 to 19 (90.48%) students who completed meeting 2 of the 2024/2025 academic year.